PURITANISM, ROMANTICISM, AND REASON AS REFLECTED IN THREE MAIN CHARACTERS OF NATHANIEL HAWTHORNE’S THE SCARLET LETTER - Nasrum, Nasrum (Elite : English and Literature Journal, 2017)
Abstract This writing is to identify the description and form of Puritanism, Romanticism and Reason found in Nathaniel Hawthorne’s The Scarlet Letter. Method used in this research is descriptive qualitative through library research with dynamic structuralism. Furthermore, the result expected is to find out description through Puritanism, Romanticism and Reason analysis on the three characters in The Scarlet Letter. Puritanism in The Scarlet Letter is showed by the society condition where people have pure transcendental relationship to the God. Romanticism is revealed by love relationship, individual freedom, passionate and happiness that related to overwhelming feeling. Reason in The Scarlet Letter is depicted by the three characters’ struggle in pursuing happiness with their reasonable actions even thoughthe societyhas not beenable toaccept it. Abstract Tulisan inibertujuan untukmengetahui gambarandanbentukPuritanisme, Romantisme danAlasan pada novel The Scarlet Letter karya NathanielHawthorne.Metode yang digunakandalam tulisan ini adalah metode deskriptif kualitatif melalui studi kepustakaandengan teoristrukturalisme dinamik.Selain itu, hasil yang diharapkanadalah untukmengetahui gambaranPuritanisme, RomantismedanAlasanpada tigakarakter utama dalamThe Scarlet Letter.Puritanismedalam TheScarlet Letterditunjukkan dengankondisimasyarakat yang memilikihubungantransendentalmurni kepada Tuhan.Romantisme diungkapkan lewathubungan cinta, kebebasan individu, kegairahan dankebahagiaan yangberkaitan denganperasaan yang luar biasa.Alasan yang muncul di novel ini digambarkanolehperjuangantiga karakter utama dalam menggapai kebahagiaanmelaluitindakan beralasan yang menurut mereka sudah tepat dilakukan meskipun masyarakat belum mampu menerimanya.